Antibiotic resistance and R-factors in the fecal coliform flora of urban and rural dogs. - Monaghan, C (1981)
The incidence of antibiotic-resistant fecal coliforms in the rectal flora of 106 healthy dogs in the Galway area was investigated. As far as could be determined, none of the dogs had received antimicrobial drugs. Half of the dogs sampled were from homes within the city boundaries, whereas the remainder were from farms within a 40-mile (24.8-km) radius of the city. Of the dogs sampled, 47 had a highly susceptible fecal coliform flora, with less than 1% of the coliform population resistant to any of the four test antibiotics. Fecal coliforms resistant to one or more of the test drugs comprised between 40 and 100% of the total fecal coliform population of 36% of the rural dogs and 13% of the urban dogs sampled. Of the 473 resistant Escherichia coli isolates studied, the highest number of associated resistance determinants encountered was 5, with a medium number of 2.5. Of the E. coli isolates from rural dogs, 52% were resistant to three or more antibiotics compared with 37% of the isolates from urban dogs. A total of 64% of the isolates were shown to transfer some or all of their resistance determinants by conjugation. The transferability of ampicillin (77%) and chloramphenicol (70%) resistance determinants was higher than that of streptomycin (40%) or tetracycline (44%).